Analysis of Consumer Perceptions and Motivations in Electric Vehicle Purchases in Indonesia - Hudha Pramudya Murti; Lutfi Ayu Faradiza; Imroatul Khasanah (LifeSciFi, 2025)
The rapid growth of electric vehicles (EVs) in Indonesia reflects that Indonesians have an increasing concern about environmental issues. This study aims to analyze the factors that influence consumers' purchase intention towards EVs, focusing on perceived ease of use, perceived usefulness of technology, and environmental awareness. This study adopts the Technology Acceptance Model (TAM) approach that includes two main variables-Perceived Ease of Use (PEU) and Perceived Usefulness (PU)-and extends the model by adding the variable Environmental Awareness (EA). Through this approach, research seeks to uncover how the combination of perceived technology and environmental awareness affects interest in electric vehicles. The findings of this study are expected to provide practical contributions for industry players and policy makers in formulating marketing strategies and policies that support the acceleration of EV adoption in Indonesia as a step towards environmental sustainability.